Bu Nyai Novelis And Bu Nyai Boardings-Based Economics: A Study of Bu Nyai Boardings-Style Economization In Indonesia - Sopiyatun, Sopiyatun; Abidin, Munirul; Ekowati, Vivin Maharani (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: The Paper is to study Bu Nyai novelist as the economic based of Bu Nyai based Islamic boarding schools in IndonesiaDesign/Method/Approach: This study the authors used a literature review that departed from existing literature studies, could be social media, existing books and journals, research was qualitative and data presentation used descriptive analysis, one of the approaches used was the historical approach to reveal the biographies of the three figures appointed in this paper, and several media-based observations to read and present the data used in this study. These methods were conducted to look at the Islamic boarding school economic network/ Bu Nyai Islamic boarding school based economization in Indonesia.Findings: This research has the following conclusions: First, the role of Bu. Nyai in the field of science and technology has been opened and the impact of progress in science and technology is not only for Bu Nyai, but also Pak. Kyai, Bu. Nyai's role in the field of employment is increasing, and Islamic boarding schools provide space for women to move. Not nyai in developing science and technology and involvement in the field. Second, the role of Bu. Nyai as a wife which includes being a wife which includes helping her husband, clearing up household affairs, using money functionally, maintaining healthy social relationships or relationships, maintaining and developing family relationships and fulfilling the function of a wife towards her husband as well as possible. Bu Nyai's role as a mother is to fulfill children's needs, as an example or model for her children, as a stimulus for child development, and as a public figure, and the roles of Bu Nyai and Pak Kyai in the domestic sphere are broadly balanced, except in the matter of roles especially the wife who is in charge of women's biological needs.Originality/Values: The main contribution of this study what is Bu Nyai's public role in the economic perspective of Islamic boarding schools, and what is the domestic role of Bu Nyai Novelis in the perspective of Islamic boarding schools.